EVALUASI KETERAMPILAN STORYTELLER DALAM MENYAMPAIKAN CERITA PADA ANAK USIA DINI DI TAMAN KANAK-KANAK RUMAN - Febriani, Putri Rizki; Zikrayanti, Zikrayanti; Hasan, Nurhayati Ali (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to determine how the storyteller's skills are in conveying stories to early childhood and what are the obstacles for storytellers in improving storytelling skills in early childhood at the Rumah Baca Aneuk Nanggroe Kindergarten. This study uses a qualitative research method. The data collection method uses observation, interview and documentation techniques. The subjects in this study were 2 storytellers at the Rumah Baca Aneuk Nanggroe Kindergarten. The results of this study indicate that storytellers only master 2 of the 6 skills that should be implemented when carrying out storytelling activities. Storytellers at the Rumah Baca Aneuk Nanggroe Kindergarten also face obstacles in improving their skills, especially in terms of their minimal experience and having never participated in various storytelling training either from schools or from other elements